Iberian atmospheric dynamics and large forest fires in mainland Portugal - Leite, Flora Ferreira (2017)
In Portugal the natural cycle of fire has been reduced, fires have become recurrent, their intensity and expansion have increased, and they have taken on catastrophic proportions. From 2003 to 2012, were accounted, for Portuguese mainland territory, 31 “large forest fires” (LFF) larger than 5000 ha (12 of them with an area exceeding 10,000 ha), and these always occurred in the months from July to September. Although the relationship between atmospheric dynamics, certain synoptic situations and the occurrence of LFF is already known in Portugal, several authors tried to identify the most favorable, in the new fire reality, that can even configure the existence of a new fire regime in Portugal, it is essential to identify synoptic patterns associated with LFF (5000 ha above), which could be an important meteorological tool in the management of wildfires.